The effect of robotic coding education on preschoolers’ problem solving and creative thinking skills - Çakır, Recep; Korkmaz, Özgen; İdil, Önder; Uğur Erdoğmuş, Feray (Thinking skills and creativity, 2021)
•Robotics and coding instruction has provided statistically significant contribution to preschoolers’ problem-solving skills compared to the pen and paper activities.•Imagination and originality factors in the language domain as well as completion, new elements addition, and unconventionality factors in the drawing domain were found to be statistically significant compared to the other factors.•According to the results of this study, there is evidence to suggest that considering the technological era in which we live, these kinds of robotics and coding activities should be integrated into preschoolers’ curriculum. The purpose of this study was to determine the effect of robotics and coding instruction on preschoolers’ problem-solving skills and creative thinking abilities. Designed as a quasi-experimental research with pretest–posttest control groups, this study was conducted in a preschool in Amasya province of Turkey. A total of 40 preschool students were recruited in this study. The data were collected through ‘the Problem-Solving Skill Scale (PSSS)’ and ‘the Creative Thinking Abilities Test’. The experimental procedure lasted for four weeks, and a total of 32 -h lesson was conducted. During the procedure in the experimental group, WeDo 2.0 Educational Robotics Kit was employed, while pen and paper activities were conducted in the control group. The participants in the experimental group performed ‘GlowingSnail’, ‘Moovingsatellite’, ‘Spacecraft’, ‘Milo Science’, ‘Milo’s Motion Sensory Robot’, and ‘Frog Robot’ activities, whereas those in the control group read such stories as ‘Winnie the Witch under the Sea’, ‘Where Do Emotions and Broken Hearts Go’, ‘the Aliens Activity’, and ‘Timing, and listened to ‘the Planets’ song. The results show that robotics and coding instruction has provided statistically significant contribution to preschoolers’ problem-solving skills compared to the pen and paper activities. Further, imagination and originality factors in the language domain as well as completion, new elements addition, and unconventionality factors in the drawing domain were found to be statistically significant compared to the other factors. Several limitations and recommendations are provided.